2016
DOI: 10.1080/02699052.2016.1213421
|View full text |Cite
|
Sign up to set email alerts
|

Does progesterone improve outcome in diffuse axonal injury?

Abstract: Findings of this study suggest that progesterone may be neuroprotective in patients with DAI. However, large clinical trials are needed to assess progesterone as a promising drug in DAI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Despite extensive investigations [12][13][14], sucssessful treatment for TBI has not yet been reported [3].…”
Section: Introductionmentioning
confidence: 99%
“…Despite extensive investigations [12][13][14], sucssessful treatment for TBI has not yet been reported [3].…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Fig. 2 , three studies showed a significant individual RR (p < 0.05) favoring the treatment group 32 , 34 , 37 .
Figure 2 Meta-analysis including 15 studies evaluating the effect of drugs with anti-inflammatory properties on a favorable outcome in TBI patients.
…”
Section: Resultsmentioning
confidence: 82%
“…As shown in Fig. 2, three studies showed a significant individual RR (p < 0.05) favoring the treatment group 32,34,37 .…”
Section: Resultsmentioning
confidence: 82%
“…Forty‐eight patients with axonal injury randomly received progesterone treatment within 4 hr of injury. Here, the progesterone group showed significantly better results than the control group (Soltani et al, ). In this context, it is believed that progesterone modulates the level of cytokines and reduces oxidant activity (Mofid et al, ).…”
Section: Progesterone and Prsmentioning
confidence: 85%